Public-Private Partnership as a tool for crisis management in the construction industry - Kalinin, O.; Gonchar, V. (Ways to Improve Construction Efficiency, 2024)
Public-private partnerships (PPPs) are becoming an increasingly important tool for infrastructure development, improving the quality of public services, and stimulating economic growth in Ukraine. The article analyzes the current state of PPP in Ukraine, identifies the main problems, proposes elements of crisis management, and outlines the prospects for the development of PPP in the future. The types and terminology of PPP contracts are studied. The main characteristics of PPPs in Ukraine are provided, including: duration of contracts: 20-30 years, which provides an incentive for the private party to take into account the costs of providing services at the stage of project development; types of projects, responsibilities of the private party; payment mechanism. A key feature of PPPs is that the assets or services provided are defined in terms of outcomes rather than inputs, i.e., they define what is needed rather than how to do it. The analysis of PPPs in Ukraine proved that there are a number of problems that complicate the implementation of PPP projects. The main ones are the imperfection of legislation, the lack of clear mechanisms for distributing risks, bureaucracy and corruption. During 2010-2023, Ukraine adopted a number of regulations governing public-private partnerships (PPPs) and concessions. The periods of active legislative regulation were 2010-2011 and 2019-2023. Regulations play an important role in minimizing risks and effective crisis management in this area. It is noted that there is a limited number of effective mechanisms for distributing risks between the State and private investors, which leads to the shift of the main burden to one of the parties, which reduces the attractiveness of PPPs for investors. Studies show that only 35% of PPP projects in the construction industry have adequate risk-sharing mechanisms. the structure and possible consequences of the main risks that public-private partnership (PPP) projects may face in different phases of their implementation are provided. It is recommended to take into account their importance when allocating risks. It is proved that in practice a qualitative approach to assessment is used more often. Public-private partnership is a powerful tool for infrastructure development and crisis management in the construction industry. However, for its successful implementation, it is necessary to improve the regulatory framework, increase institutional capacity and ensure transparency of processes.